2013
DOI: 10.1007/s11427-013-4459-3
|View full text |Cite
|
Sign up to set email alerts
|

BmCyclin B and BmCyclin B3 are required for cell cycle progression in the silkworm, Bombyx mori

Abstract: Cyclin B is an important regulator of the cell cycle G2 to M phase transition. The silkworm genomic database shows that there are two Cyclin B genes in the silkworm (Bombyx mori), BmCyclin B and BmCyclin B3. Using silkworm EST data, the cyclin B3 (EU074796) gene was cloned. Its complete cDNA was 1665 bp with an ORF of 1536 bp derived from seven exons and six introns. The BmCyclin B3 gene encodes 511 amino acids, and the predicted molecular weight is 57.8 kD with an isoelectric point of 9.18. The protein contai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 23 publications
0
8
0
Order By: Relevance
“…RT-qPCR was performed to confirm transcriptomic expression profilings of cyclin-like genes at different stages and tissues. Based on previous reports in B. mori and D. melanogaster [ 12 , 15 , 16 , 19 ], six ( PxCyc D3 , PxCyc B1 , PxCyc G1 , PxCyc A2 , PxCyc B3 , PxCyc D , PxCyc C2 ) genes were selected. PxCyc D3 and PxCyc G1 exhibited significantly high relative expressions in adult females, followed by adult males and eggs.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…RT-qPCR was performed to confirm transcriptomic expression profilings of cyclin-like genes at different stages and tissues. Based on previous reports in B. mori and D. melanogaster [ 12 , 15 , 16 , 19 ], six ( PxCyc D3 , PxCyc B1 , PxCyc G1 , PxCyc A2 , PxCyc B3 , PxCyc D , PxCyc C2 ) genes were selected. PxCyc D3 and PxCyc G1 exhibited significantly high relative expressions in adult females, followed by adult males and eggs.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, the DmCyc G negatively regulates the cell growth and development process since overproduction of DmCyc G results in a limited number of cells, while a lack of DmCyc G results in a large number of cells [ 18 ]. In Bombyx mori , the suppression of BmCyclin B and BmCyclin B3 expression through RNAi causes cell cycle detention at the G2 and M phases in the BmN cell line, reducing cell proliferation, which indicates that BmCyclin B and BmCyclin B3 are required for completion of the cell cycle in the BmN cell line [ 19 ]. Previous reports in D. melanogaster and B. mori suggest that cyclin-like genes are not only involved in cell cycle regulations but play significant roles in growth, development, and reproduction.…”
Section: Introductionmentioning
confidence: 99%
“…melanogaster , PEX1 mutants are lethal at different developmental stages (Deak et al ., ; Mast et al ., ). BGIBMGA003777 , another candidate gene, BmCyclin B3 (BmCycB3) , is required for cell cycle progression in the silkworm (Pan et al ., ). The identification of CycB3 in chicken ( Gallus gallus ), the nematode Caenorhabditis elegans and D .…”
Section: Discussionmentioning
confidence: 99%
“…In D. melanogaster, PEX1 mutants are lethal at different developmental stages (Deak et al, 1997;Mast et al, 2011). BGIBMGA003777, another candidate gene, BmCyclin B3 (BmCycB3), is required for cell cycle progression in the silkworm (Pan et al, 2013). The identification of CycB3 in chicken (Gallus gallus), the nematode Caenorhabditis elegans and D. melanogaster revealed that CycB3 is conserved during the evolution of higher eukaryotes (Gallant & Nigg, 1994;Kreutzer et al, 1995;Sigrist et al, 1995).…”
Section: The Probable Factors For Homozygote Lethalitymentioning
confidence: 99%
“…The BmCyclin B was necessary to complete the cell cycle in BmN cells and had revealed mitotic cell divisions function in silk gland development of embryogenesis in B . mori [ 30 , 31 ]. The Bmcyclin B mRNA, abundant in matured eggs, began to degrade sharply just after oviposition, which suggested that the penetration of sperm triggered the degradation of maternal Bmcyclin B mRNA in the first meiosis [ 25 ].…”
Section: Discussionmentioning
confidence: 99%